A method of monitoring function in corticospinal pathways during scoliosis surgery with a note on motor conduction velocities. Issue 3 (March 1986) - Boyd, S G; Rothwell, J C; Cowan, J M; Webb, P J; Morley, T; Asselman, P; Marsden, C D
Abstract : Spinal cord potentials produced by high voltage electrical stimulation of the scalp over the motor cortex were recorded intraoperatively from bipolar electrodes inserted into the epidural space of eleven patients undergoing corrective surgery for scoliosis. Responses to single stimuli could be recorded from the cord at all levels from cervical to low thoracic regions. The potentials were larger in the cervical than in the thoracic region and sometimes were followed by later waves at high stimulation intensities. Conduction velocity in large corticomotoneuron fibres was estimated to be between 50-74 ms-1 in different patients. This technique for monitoring motor tract function may be a useful adjunct to conventional monitoring of the sensory pathways during surgery.